SERS study on myeloperoxidase and its immunocomplex: Identification of binding interactions. Issue 3 (2010) - Papazoglou, Elisabeth S.; Babu, Sundar; Hansberry, David R.; Mohapatra, Sakya; Patel, Chirag
Abstract : Surface Enhanced Raman Spectroscopy (SERS) has demonstrated significant benefit in the identification of biological molecules. In this paper we have examined how to identify and differentiate the 150 kDa protein myeloperoxidase (MPO) from its corresponding antibody (Ab) and their immunocomplex through the use of SERS. The SERS signal of these biological molecules was enabled by 40 nm gold nanoparticles. The SERS spectra for both MPO and the Ab (an IgG molecule) demonstrated results consistent with previous published work on the Raman spectra of MPO and IgG antibodies. The immunocomplex SERS spectra showed peak shifts and intensity variations that could be attributed to conformational changes that occur during immunocomplex formation. Several key spectral areas have been identified which correspond to specific amino acids being shielded from undergoing resonance while new amino acid residues are made visible in the SERS spectrum of the immunocomplex and could be a result of conformational binding. These results indicate that SERS can be used to identify binding events and distinguish an immunocomplex from its individual components.